UPAYA HUKUM PENANGGULANGAN PENGAKSES SITUS INTERNET YANG MEMUAT UNSUR PORNOGRAFI OLEH KEMENTERIAN KOMUNIKASI DAN INFORMATIKA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In a modern global society like today, crime can be committed anywhere, both in the real space and in cyberspace. This happens because the era of globalization has opened up several opportunities for the occurrence of crime, so that a joint response is needed through cooperation between interested parties. Advances in technology can not be dammed and very easy to access all kinds of information needed, here are some positive impacts of the advancement of information technology. However, behind these positive impacts can also be negative impacts that are very worrying about the development of young people and children because the impact of pornographic videos is very damaging to the mental development of these children.This type of research can be classified in the type of Normative legal research, which reveals legislation relating to legal theories that are the object of research. The approach taken uses a qualitative analysis approach by looking for data both in books, journals and other scientific works related to this research. The data sources used are primary and secondary legal materials.The conclusions that can be obtained from the results of the study are First, the Efforts to Prevent the Access of Internet Sites that Contain Pornographic Elements by the Ministry of Communication and Information have been carried out with a clear legal basis. However, the application of legal policy making to the response there are still weaknesses because they do not use the principles of legal policies that can determine the direction in implementing the principle of countermeasures. Second, the factors which are inhibiting the Ministry of Communication and Information in handling the access of internet sites that contain pornography are divided into elements; website, application, bulging site. Third, the Form of Efforts to Overcome Obstacles in Handling of Accessing Internet Sites that Contain Pornographic Elements by the Ministry of Communication and Information contains 3 things; Image filtering, sensor engine and access filterKeywords: Countermeasures, Criminal Acts, Pornography, Ministry of Communication, ITE.